Proses Transesterifikasi Biji Minyak Jarak Dengan Bantuan Enzim Lipase Sebagai Penghasil Biodiesel - Yusafir Hala; Muh. Zulkifli Jufri; Astina Tambung (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2009)
The investigation was carried out to prevent the scarce of fosil based fuel. In this investigation used seed of castor oil plan (Jathropha curcas L.) as natural row material to make castor oils and converted to biodiesel so that it’s friendly to the biological environment. Castor oils produced by extraction process with soxhletation methods used n-hexane solvent. The result of extraction then converted to biodiesel by transesterification process at optimum temperature 40o C with methanol and catalyzed with lipase enzyme. Free fatty acid analysis and total fat analysis was done to the result product, and then biodiesel converted value as 88.67% gotten. Some characteristics analysis of biodiesel castor oils like density, viscosity, pouring point, flaming point, and caloric value according ASTM D6751. The result of investigation showed castor oils biodiesel can be used as diesel fuel.Keywords : fuel, castor oils, biodiesel, transesterfication, and optimum temperature.